Cellular localization of NGF and NGF receptors in aged human thymus - Marinova, T; Velikova, K; Philipov, S; Stankulov, I; Chaldakov, G; Aloe, L (Folia biologica, 2003)
Recent evidence indicates that some thymic cells of developing and adult laboratory animals express the neurotrophin NGF and its low-affinity p75NTR and high-affinity TrkA receptor. Less is known as to whether the thymus of adult and aged humans express these markers. We hypothesize that the presence and distribution of immunopositive cells for NGF and NGF receptors undergo some alterations during the involution of human thymus. Specimens from normal thymuses of old individuals were obtained from autopsy and surgery cases, and examined immunocytochemically at the light and transmission electron microscopic level. The immunoreactivity of NGF, p75NTR, TrkA and cytokeratin was found in the epithelial thymocyte microenvironment. Our results provide the first ultrastructural evidence for NGF/receptor immunocytochemical localization in human thymus. They suggest a possible immunotrophic/immunoregulatory role of the NGF-p75NTR-TrkA system for T-cell development in human thymus during senile involution.
Keywords: senioři; receptor trkA; Receptor, trkA; Nerve Growth Factor; Aging; receptory faktorů růstu nervů; Receptors, Nerve Growth Factor; mladiství; imunohistochemie; mužské pohlaví; Receptor, Nerve Growth Factor; Immunohistochemistry; stárnutí; nízkoafinní receptor faktorů růstu nervů; Humans; nervový růstový faktor; Thymus Gland; thymus; Aged; Adolescent; lidé; Male